1985
DOI: 10.1111/j.1540-4560.1985.tb01114.x
|View full text |Cite
|
Sign up to set email alerts
|

Applying Social Support Research: Theoretical Problems and Future Directions

Abstract: Two independent research traditions have evolved that deal with social support‐an analytic tradition that emphasizes theory‐based tests of hypotheses and an applied tradition that emphasizes evaluations of interventions. This paper seeks to stimulate feedback between these two traditions by examining how implicit assumptions and conceptual distinctions embedded within the analytic literature translate into suggestions for intervention. Assumptions that bear on the soundness of undertaking interventions of any … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
50
0
4

Year Published

1994
1994
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(54 citation statements)
references
References 53 publications
0
50
0
4
Order By: Relevance
“…The relationship between perceptions of support and support actually received is only moderate (Barrera, 1986;Bianco & Eklund, 2001;Dunkel-Schetter & Bennett, 1990), and the receipt of support does not necessarily lead to an increase in perceived support (Rook & Dooley, 1985). On the other hand, Norris and Kaniasty (1996), using a longitudinal design, found that received support did affect perceived support over time.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between perceptions of support and support actually received is only moderate (Barrera, 1986;Bianco & Eklund, 2001;Dunkel-Schetter & Bennett, 1990), and the receipt of support does not necessarily lead to an increase in perceived support (Rook & Dooley, 1985). On the other hand, Norris and Kaniasty (1996), using a longitudinal design, found that received support did affect perceived support over time.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the relationship between vulnerability to stress and variables such as social support (Cohen & Wills, 1985;Rook & Dooley, 1985), coping skills (Elias et al, 1986), and the preservation of roles (Heller, 1990) has given rise to considerable research and lively controversy. The continuity principle stresses the permanence and coherence of the different factors, rather than their presence or absence.…”
mentioning
confidence: 99%
“…Schlossberg, Waters et Goodman (Schlossberg, 2005 ;Schlossberg, Waters & Goodman, 1995), dont Gingras et Sylvain (1998) ont exposé la conception générale dans la présente revue, reconnaît aux soutiens sociaux un poids considérable dans les transitions professionnelles et personnelles. Les soutiens sociaux sont généralement étudiés du point de vue de la perception qu'en ont les individus et des corrélations de celle-ci avec différents paramètres de l'adaptation (voir par exemple Rook & Dooley, 1985). Les processus en jeu dans la transaction interpersonnelle par laquelle est fourni le soutien social sont plus rarement analysés.…”
unclassified